Multicenter Mid-Term Outcomes of the Chimney Technique in the Elective Treatment of Degenerative Pararenal Aortic Aneurysms. (April 2022) - Pitoulias, Georgios A.; Fazzini, Stefano; Donas, Konstantinos P.; Scali, Salvatore T.; D'Oria, Mario; Torsello, Giovanni; Veith, Frank J.; Puchner, Stefan B.
Purpose: Chimney endovascular abdominal aortic aneurysm repair (CHEVAR) has predominantly been described as an alternative technique for the management of urgent presentations of degenerative pararenal aortic aneurysms (dPAAs). However, the role of CHEVAR in the treatment of asymptomatic patients remains unknown. The aim of current multinational study was to evaluate the outcomes of elective CHEVAR of dPAAs. Material and Methods: Retrospective analysis of 267 consecutive dPAA patients treated with elective CHEVAR at 13 European and US centers from 2008 to 2014. Primary endpoints were 30 days and out of hospital CHEVAR-related mortality. Secondary endpoints included persistent type Ia endoleak or endotension, angiographically confirmed occlusion and/or high-grade chimney graft (CG) or involved splanchnic vessel stenosis identified at index procedure and/or during follow-up, as well as CHEVAR-related re-intervention. Results: Mean follow-up time was 25.5±13.3 months. The 442 visceral vessels were involved and mean number of CGs per patient was 1.63±0.7. 436 targeted vessels were successfully cannulated. The aortic graft intentionally covered 6 renal arteries and immediate technical success was 98.6%. The 30 days mortality was 1.9% (n=5), while the in-hospital complication rate was 10.1% (n=27) including 3 strokes, 1 permanent dialysis, and 1 intestinal ischemia. No 30 day type Ia endoleaks were detected and 3.2% of CGs (n=14, including the intentionally covered) had evidence of occlusion and/or stenosis. The overall CHEVAR-related mortality was 2.2% (n=6). Freedom from primary and secondary type Ia endoleak/endotension rates at 3 years was 93.0% and 98.0%, respectively. Primary and secondary CG patency was 87.0% and 89.0%. Primary and secondary endovascular freedom from any endpoint at 3 years was 81.0% and 94.0% respectively. Conclusion: Elective use of CHEVAR in the management of dPAAs seems to be durable. These results are comparable to published outcomes with other total endovascular strategies, which justifies an expanded role for CHEVAR in the treatment of asymptomatic patients presenting with dPAAs.